Signaling in deterministic and stochastic settings - Thomas D. Jeitschko; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
We contrast a standard deterministic signaling game with one where the signal-generating mechanism is stochastic. With stochastic signals a unique equilibrium emerges that involves separation and has intuitive comparative-static properties as the degree of signaling depends on the prior type distribution. With deterministic signals both pooling and separating configurations occur. Laboratory data support the theory: In the stochastic variant, there is more signaling behavior than with deterministic signals, and less frequent types distort their signals relatively more. Moreover, the degree of congruence between equilibrium and subject behavior is greater in stochastic settings compared to deterministic treatments.
Keywords: C7; C9; D8; 330; experiments; learning; noise; signaling; stochastic environments